Administration of Sugar Factory Equipment Repair Services - Dia Setiawati; Dyah Widowati (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
Administration has a strategic role in supporting the efficiency and effectiveness of company operations, especially in the sugar industry equipment repair sector. The study aims to determine the application of administration in supporting sugar factory equipment repair services by Nusantara Maintenance Facilities (NMF) at PG Djombang Baru. The data collection techniques used were interviews and literature studies, which were to explore the importance of structured administration to ensure smooth operations. Administration at Nusantara Maintenance Facilities has been implemented in a structured manner and in accordance with standard operating procedures (SOP) and is able to support operational needs. However, there are still some aspects that need to be improved, such as strengthening communication between technical and administrative teams.